(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article considers modern neurophysiological methods of studying pain syndromes of the maxillofacial region (MFR). It is shown that in recent years, clinical and neurophysiological features of various types of chronic facial pain, as well as the functional state of afferent systems and mechanisms of interaction of afferent and efferent pathways in chronic pain have been actively studied. The possibilities of neurophysiological study of the trigeminal system for establishing the pathogenesis of pain syndromes of the MFR are analyzed.